Reaction between harmaline and vanillin to produce dimeric scaffolds that exhibit anti-proliferative activity. (8th June 2021) - Birar, Vishal C.; Zaid, Gene; Blagg, Brian S.J.
Graphical abstract: Highlights: Dimers of the natural product, harmaline, exhibit anti-proliferative activity. Preliminary structure–activity relationships revealed the linker to be important for biological activity. New compounds derived from the combination of other natural products may represent a new approach toward molecular diversity. Abstract: Herbal medicine is used as a complement to modern medicine for the treatment of human diseases such as cancer, inflammation, and diabetes. Nutraceutical components in foods such as vanillin produce antioxidant and anticancer activities and many of these produce minimal adverse effects in humans. Therefore, strategies that combine both herbal medicine and nutraceutical components could produce compounds that exhibit reduced toxicity. Recently, we developed GZ16.007, which is a combination of harmaline and curcumin that is currently undergoing clinical evaluation for the treatment of cancer. In contrast to the utilization of curcumin, we report herein the synthesis of a novel scaffold that utilizes harmaline and vanillin as nutraceutical components to form a newly identified anti-cancer scaffold. It was determined that the inclusion of two molecules of harmaline and a single equivalent of vanillin produced a dimeric product that was active against various human cancer cell lines. The synthesis, evaluation and preliminary SAR studies for the dimeric scaffold is discussed herein.